An effort to enhancing consumer purchase intention post-COVID 19 in the pilgrimage and small-pilgrimage service provider of BONITA - Habil Fuady; Dessy Kurnia Sari; Donard Games (Institute of Computer Science (IOCS), 2022)
In recent days, there has been an increasing interest towards achieving sustainable global tourism objectives specifically to Saudi Arabia. The benefits can be maximized if the government is successful in attracting current pilgrims and influence their future intention to visit the country as tourists through the service provider in Muslim countries. Hence, the purpose of this paper is to measure pilgrims’ and small-pilgrimage’s purchase intentions by the effect of electronic word of mouth, price, and brand image through mediating model on service providers in Indonesia. By the technique of purposive with two criteria, we received as many as 80 online questionnaires returned, and it then conducted data analysis by assisting Smart PLS latest version. Results stated that price didn’t affect any outcomes, while E-WOM effects are in line with expectation.